IMPACT OF POLYMORPHISM OF CARDIOVASCULAR RISK GENES ON ARTERIAL REMODELLING DEVELOPMENT DEPENDING ON PRESENCE OF SYSTEMIC HYPERTENSION - A. I. Chernyavina; M. V. Surovtseva (Российский кардиологический журнал, 2018)
Aim. To investigate on clinical and genetic characteristics of patients with multiple cardiovascular risk factors depending on the presence or absence of arterial hypertension (AH) and severity of pure arterial stiffness.Material and methods. To the study, 330 patients of economically active age were included, with multiple cardiovascular risk factors at one of Perm city factories. Mean number of the risk factors 5,25±1,04. Mean age 46,67±8,46 y. o. Among the participants 205 (62,12%) males and 125 (37,88%) females. In 177 (53,6) there was AH of grade 1-3 diagnosed. All participants underwent genotype assessment by the markers AGT Thr174Met rs4762, GNB3 C825T rs5443, MTHFR C677T rs1801133, MTRR Ile22Met rs1801394, ApoE Cys130Arg rs 429358, PPARα G/C rs4253778; volume sphygmopletysmography with the CAVI1 measurement. In the first part of the study, patients were selected to 2 groups according to AH presence. In the second part — by CAVI1 level, selected to 3 subgroups: 1st subgroup — no lesion of arteries and CAVI1 <8, 2nd subgroup — borderline arteries lesion and CAVI1 8-8,9; 3rd subgroup — serious arteries lesion and CAVI1 >9.Results. Among the patients with borderline arteries lesion with AH or with none, the most significant are genotypes С/Т and ТТ of polymorphism Thr174Met rs4762 gene AGT, genotypes С/Т and Т/Т of polymorphism C825T rs5443 gene GNB3, genotypes С/Т and Т/Т of polymorphism C677T rs1801133 gene MTHFR, and genotypes С/С of polymorphism G/C rs4253778 gene PPARα. In patients with the CAVI1 >9 also, regardless of AH presence, were significant the С/Т and ТТ polymorphism Thr174Met rs4762 of gene AGT, genotypes С/Т and Т/Т polymorphism C677T rs1801133 gene MTHFR, genotypes A/G and G/G of polymorphism Ile22Met rs1801394 gene MTRR, and genotype G/С and С/С polymorphism G/C rs4253778 gene PPARα. Presence of AH with no target organ lesion is associated with С/Т polymorphism of the gene GNB3, genotype Т/Т polymorphism of gene MTHFR, and genotypes G/С and С/С of gene polymorphism PPARα. Correlational analysis showed moderate direct correlation of CAVI1 and polymorphism of the genes AGT (r=0,35; p=0,022), GNB3 (r=0,43; p=0,029), MTHFR (r=0,42; p=0,002), MTRR (r=0,43; p=0,025), PPARα (r=0,39; p=0,036). Relation with САVI1 and gene polymorphism АроЕ was not significant.Conclusion. The study witness on the fact that cardiovascular risk shaping and the development of arterial stiffness depend not only on blood pressure level, but patient’s genotype. The data showed that some definite genotypes can be regarded as early markers of cardiovascular risk and arteries lesion in AH patients, and in no AH as well.